DESIGN, OPTIMIZATION AND EVALUATION OF RANOLAZINE FAST-DISSOLVING FILMS EMPLOYING MANGO KERNEL STARCH AS A NEW NATURAL SUPERDISINTEGRANT - DEVI, MEDISETTY GAYATRI; R, SANTOSH KUMAR (International Journal of Applied Pharmaceutics, 2024)
Objective: The BCS class II cardiovascular medication, Ranolazine (RZN), is characterized by limited solubility and inadequate oral absorption. The objective of the current research is to develop a natural superdisintegrant in the formulation of Fast-Dissolving Films (FDFs) of Cardio Vascular Drug (CVD) RZN to enhance its dissolution rate, solubility, absorption, and therapeutic action. Methods: Mango Kernel Starch (MKS) is isolated by grinding the kernels, forming a slurry with water, filtering, and using repeated centrifugation and washing to purify the starch, which is then dried. The obtained starch is collected. Along with obtained natural superdisintegrant MKS, Maltodextrin (MDX) and Sodium Starch Glycolate (SSG) were also utilized in the fabrication of FDFs containing RZN via the solvent casting technique. A total of eight formulations (RF1 to RF8) were developed employing a 23 factorial design, using the natural superdisintegrant alone at a concentration of 5% and in combination with other superdisintegrants. Results: The prepared MKS was found to be free-flowing, fine, amorphous, insoluble in organic solvents, and exhibiting 0.17% solubility in water with a swelling index of 89.95%, indicating superdisintegrant properties. Fourier-transform infrared spectroscopy (FTIR) studies and Differential scanning calorimetry (DSC) analysis indicated that there was no drug-excipient interaction. The films prepared with a 5% concentration of the MKS showed good physical properties and resulted in an increased drug dissolution rate, with 99.78 % of the drug dissolved within 10 min, along with the lowest disintegration time of 13.45 sec. Conclusion: The research successfully isolated a new superdisintegrant, MKS and formulated FDFs of the poorly water-soluble drug RZN. The MKS was found to be an effective superdisintegrant with no drug interactions, producing films with good physical and mechanical properties, increasing the drug dissolution rate, and providing rapid disintegration with improved relative bioavailability.